Dignitaries-Ervin, Sam-0001
Visit of Senator San Ervin to Fresno State (L to R) James Bill, Prsident Fresno Bar Association; Senator Ervin; Judge Harold Thompson Chairman CSUF Advisory Board; President Baxter